2020
DOI: 10.1177/1049732320944141
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Mothers’ Expectations and Experiences of Postnatal Care in England

Abstract: Postnatal care is the aspect of maternity care with which women in England are least satisfied. Little is known about first-time mothers’ expectations of postnatal care, or how these expectations relate to their experiences and appraisal of care. Thirty-two first-time mothers took part in a longitudinal qualitative descriptive study, based on two semi-structured interviews—the first in pregnancy, and the second 2 to 3 months after birth. Trajectory analysis was used to identify the thematic patterns in the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“… 33 While first time mothers are less confident, and perceive themselves as requiring much support, a woman with multiple births may be less concerned about childhood ailments that have been exhibited by her child in the past. 34 Maternal health workforce of SSA may be able to neutralise this disparity by acknowledging that anxieties and maternal healthcare utilisation levels vary by parity. Among the numerous strategies to improve the situation include targeting and educating multiparous women to appreciate that all children who miss any dose of immunisation stand a chance of ill health conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 33 While first time mothers are less confident, and perceive themselves as requiring much support, a woman with multiple births may be less concerned about childhood ailments that have been exhibited by her child in the past. 34 Maternal health workforce of SSA may be able to neutralise this disparity by acknowledging that anxieties and maternal healthcare utilisation levels vary by parity. Among the numerous strategies to improve the situation include targeting and educating multiparous women to appreciate that all children who miss any dose of immunisation stand a chance of ill health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This provides strong evidence that COVID-19 lockdown restrictions have had an adverse cumulative effect on maternal mental health. Howbeit, using a modified analytical approach was an identified limitation of the current study, deviating from reported procedures in previously published perinatal literature whereby repeat interviewing had been reported [45]. This is problematic because lack of homogenous sampling at independent timepoints may have unintentionally compromised methodological rigour.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 97%
“…But the fact that these postings were easily found in online searches, are still available, and come up alongside more formal sources means that they warrant study and consideration. We know that women build their knowledge from multiple sources ( Hinton et al, 2018 ; McLeish et al, 2020 ; Sunstein, 2001 ), so what is happening in these spaces informs the whole. There was a variety of tone.…”
Section: “Any Advice?” “I Don’t Really Know What I’m Talking About But I Just Wanted To Offer Some Reassurance” Medical Expertise Contestmentioning
confidence: 99%